Taking care of the forest and the environment (Barama Company Limited GeorgetownGY, 1993)
Highlights Barama's Forest Management Plan, and the role of the Edinburgh Centre for Tropical Forests, in which it will monitor Barama's forest activities and assist in the periodic updating of the forest management plan.
DC